Taxonomia, diversidade e bioprospecção de fungos endofíticos associados à planta medicinal Lafoensia pacari A. St. Hil. (mangava-brava) presente no Pantanal Mato-grossense - Soraya Sander Amorim (2018)
Endophytes are microorganisms that inhabit plant tissues during at least one stage of their life cycle and they do not cause any apparent symptom of disease on their hosts. They play important ecological and physiological roles in the interaction with their host plants and are a potential source of bioactive secondary metabolites of pharmacological and agricultural interest. The criteria for the selection of the target host species is a choice of medicinal plants and those that occur in regions of great biodiversity. Lafoensia pacari, a medicinal plant found in the little studied Pantanal Mato-Grossense, used for the treatment of gastric disorders by macerating the leaves and the bark. Considering the above, this work aims to characterize the community of endophytic fungi associated with L. pacari, as well as evaluating it as a source of antiparasitic, antiviral and herbicidal metabolites. From the fragments of leaves, bark and seeds of L. pacari, 236 filamentous fungi and 3 yeasts were isolated. They were identified by sequencing the internal transcribed region ITS-5.8S of the rRNA gene region, as well as by the partial sequencing of the â-tubulin gene. Yeasts were subjected to sequencing of the D1/D2 domains of the major subunit of ribosomal DNA. A total of 60 filamentous fungal taxa and tree yeast taxa were obtained, represented by the classes Dothideomycetes, Sordariomycetes, Eurotiomycetes, and Saccharomycetes (Ascomycota); Ustilaginomycetes (Basidiomycota); and Zygomycetes (Zygomycota). The most abundant genera were Phyllosticta, Diaporthe, Lasiodiplodia, Colletotrichum, Pseudofusicocum, Aspergillus and Penicillium. Lafoensia pacari seeds were germinated in the Murashige & Skoog (MS) and Wood plant (WP) media for the isolation of their true endophytes from the seedlings and nine isolates were obtained in the taxa Cladosporium sp. 1, Cladosporium sp. 2, Aspergillus sp. and Eremothecium gossypii. The diversity of the endophytic fungi community associated with L. pacari was high, with higher taxonomic richness values and lowest taxonomic dominance. For the seedlings, these indexes were lower, indicating lower diversity and higher dominance. The production of bioactive secondary metabolites was evaluated. Dichloromethane crude extracts were produced from all fungal isolates obtained from the leaves and barks of L. pacari. The isolates obtained from the seedlings cultured in vitro were extracted with ethyl acetate. All extracts were submitted to biological assays to evaluate antiparasitic, antiviral and herbicidal activities. No extract showed activity against Leishmania amazonensis and the dengue virus. Four extracts belonging to taxa Aspergillus aculeatus, Coniothyrium sp. and Valsariaceae sp. were active against Trypanosoma cruzi, which present high efficiency and low cytotoxicity, because this the extracts were considered promising for the isolation of trypanocidal compounds. The extracts were also evaluated for herbicidal activity against the seeds of Latuca sativa (lettuce) and Allium schoenoprasum (chives). Forty nine extracts showed herbicidal activity, and 14 inhibited 100% of the germination of the both models used at the assay. Among the bioactive fungi, three true endophytes showed herbicide activity for lettuce. From the results obtained it is verified that the medicinal plant L. pacari represents a promising reservoir of diversified endophytic fungi capable of producing bioactive metabolites that can be used for both therapeutic and agricultural purposes.